2008
DOI: 10.1089/zeb.2007.0517
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafishwnt9bSynteny and Expression During First and Second Arch, Heart, and Pectoral Fin Bud Morphogenesis

Abstract: Roles for Wnt9b in craniofacial development are indicated by the cleft lip mutant phenotype observed in the A=WySn mouse strain, 1 caused by a retrotransposon insertion mutation at the Wnt9b locus. Analyses of the zebrafish Wnt9b ortholog, wnt9b, were pursued to provide insight into early vertebrate craniofacial patterning events mediated by Wnt9b signaling. Zebrafish wnt9b cDNA clones were isolated and found to encode an open reading frame of 358 amino acids, with 68% amino acid identity to mouse Wnt9b and 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Our prior report of Wnt9b expression demonstrates Wnt9b is expressed maternally, early zygotically and even later during zebrafish craniofacial development [41]. Of particular note Wnt9b is expressed within the first pharyngeal arch (PA1) ectodermal epithelia during the time when CNCC are patterned by the edn1 pathway from Dorsal-Ventral subdomains into Dorsal-Intermediate-Ventral domains.…”
Section: Loss Of Wnt9b Activity Results In Multiple Craniofacial Phenmentioning
confidence: 98%
See 3 more Smart Citations
“…Our prior report of Wnt9b expression demonstrates Wnt9b is expressed maternally, early zygotically and even later during zebrafish craniofacial development [41]. Of particular note Wnt9b is expressed within the first pharyngeal arch (PA1) ectodermal epithelia during the time when CNCC are patterned by the edn1 pathway from Dorsal-Ventral subdomains into Dorsal-Intermediate-Ventral domains.…”
Section: Loss Of Wnt9b Activity Results In Multiple Craniofacial Phenmentioning
confidence: 98%
“…In zebrafish, we and others showed that Wnt9b is expressed maternally and during early zygotic phases [41]- [43]. Later, from about one day post fertilization (dpf) onwards, Wnt9b is expressed within the first pharyngeal arch (PA) ectodermal epithelia that overlies the arch's cranial neural crest cells (CNCCs), which have mostly finished their migration into the ventral half of the embryo by 24 hours post fertilization (hpf) [41].…”
Section: Wnt Growth Factor Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene expression of zebrafish wnt9b has been examined but limited signal was detected in the first and second pharyngeal arches (Jezewski et al, 2008). Study of vertebrate gene synteny identified conservation of wnt9a across human, mouse, Xenopus and zebrafish genomes (Garriock et al, 2007).…”
Section: Introductionmentioning
confidence: 99%